The Effect of Fertilizer Treatment on the Morphology of Maize (Zea mays) Planted in An Intercropping System in the Immature Oil Palm Plantation - Alhaviz, Alhaviz; Hariyadi, Hariyadi; Supijatno, Supijatno (Journal of Tropical Crop Science, 2021)
Applying and optimizing an intercropping system between oil palm and seasonal crops such as maize in the immature palm oil plantation is one way of obtaining additional income for farmers until the main crop (oil palm) mature and ready to harvest. The aim of the research was to determine the effects of fertilizers, particularly nitrogen (N) and potassium (K) on the growth and production of maize in an intercropping system with oil palm. The experiment, using one-factor randomized complete block design, was conducted at the Cikabayan Experimental Station, IPB University, Indonesia, from August to December 2020. Four set-ups were prepared corresponding to four different fertilizer applications as follows: A0 (without treatment), A1 (240 g Urea + 80 g KCl + 320 g SP-36 per plot), A2 (480 g Urea + 160 g KCl + 320 g SP-36 per plot), A3 (720 g Urea + 240 g KCl + 320 g SP-36 per plot). Applying the highest dosages of N and K (A3), significantly increased plant height, fresh weight, number of leaves, leaf area, stem diameter, cob length, cob weight, and husk-free cob weight. Intercropping maize with immature oil palm did not affect the oil palm growth.